2011
DOI: 10.1038/nn.2749
|View full text |Cite
|
Sign up to set email alerts
|

An optogenetic toolbox designed for primates

Abstract: Optogenetics is a technique for controlling subpopulations of neurons in the intact brain using light. This technique has the potential to enhance basic systems neuroscience research and to inform the mechanisms and treatment of brain injury and disease. Before launching large-scale primate studies, the method needs to be further characterized and adapted for use in the primate brain. We assessed the safety and efficiency of two viral vector systems (lentivirus and adeno-associated virus), two human promoters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
406
2
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(424 citation statements)
references
References 50 publications
11
406
2
5
Order By: Relevance
“…2). Previous optogenetic inactivation studies focusing on related brain areas have interpreted a lack of effect of transient inactivation as a lack of role in behavior 13,42 . Our results imply that redundancy across a distributed network could mask possible causal roles in optogenetics experiments.…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous optogenetic inactivation studies focusing on related brain areas have interpreted a lack of effect of transient inactivation as a lack of role in behavior 13,42 . Our results imply that redundancy across a distributed network could mask possible causal roles in optogenetics experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, FEF pharmacological inactivation studies report inactivation of volumes of ∼10 mm 3 (2, 3). Further, optogenetically driven neuronal effects in primates are often heterogeneous, decreasing the activity of some neurons and increasing the activity of others (14,(17)(18)(19). No primate optogenetics study has reported inactivation levels near the levels of FEF pharmacological inactivation studies, namely, >80% reduction in firing rate relative to baseline reported in >80% of neurons (1-3).…”
mentioning
confidence: 99%
“…However, optogenetics has provided methods to transiently, delicately, and reversibly turn molecularly identified neuronal cell types or even just their connections off and on again for time-scales lasting from milliseconds to hours. Although such invasive techniques are off-limits in humans, they are being routinely implemented in mice [5,6] and, to a much more limited extent, in monkeys [7][8][9].…”
mentioning
confidence: 99%